Positive Influence of Certain Sports on Learning and Second Language Acquisition Processes - Boyarkina, Iren (Zbornik radova Filozofskog fakulteta u Prištini, 2021)
The paper analyses positive contribution of certain sports to learning in general, and Second Language Acquisition in particular, using neuroscience, psychological and socio-cultural approaches. Various research convincingly demonstrated positive influence of certain sports and physical exercises on brain and brain functions in general, and on cognitive functions in particular. As it has been demonstrated, efficient and well-developed cognitive functions enhance all human activities and are of crucial importance for learning. In particular, this paper focuses on the positive correlation between certain sports and language learning and its relevance to the Second Language Acquisition studies (SLA).
Keywords: sports; cognitive abilities; neuroscience; language teaching; Second Language Acquisition